Safety and tolerability of subcutaneous trastuzumab and intravenous pertuzumab as adjuvant treatment for HER2 positive breast cancer: a pilot study. Issue 1163 (26th May 2021) - Wong, Chi Yan; Leung, Roland; Kwok, Gin Wai; Tsang, Josephine; Li, Bryan; Yau, Thomas; Chiu, Joanne
Abstract: Background: Subcutaneous (SC) trastuzumab is similar to intravenous trastuzumab in terms of pharmacokinetics, efficacy and tolerability. The use of dual anti-HER2 agents trastuzumab and pertuzumab has become the new standard for node-positive HER2-positive breast cancers at adjuvant setting, but the safety and tolerability of combining SC trastuzumab and intravenous pertuzumab is not well studied. Methods: This was a prospective single-arm pilot study with locally advanced HER2-positive breast cancer who received adjuvant SC trastuzumab and intravenous pertuzumab after standard anti-HER2 treatment with chemotherapy. Primary outcomes included adverse events (AEs), severe AEs and cardiac AEs. Secondary outcome was invasive disease-free survival (iDFS). Results: With a median follow-up of 21.7 months, 20 patients were enrolled. One patient (5%) developed asymptomatic drop in left ventricular ejection fraction from 69% to 53%. Two patients (10%) developed grade 1 injection site reaction related to SC trastuzumab. There were no grade 2 or above AEs. All AEs were transient. No new AEs were observed. The 1-year iDFS was 90% (95% CI 0.656 to 0.974) Conclusions: Combination of SC trastuzumab and intravenous pertuzumab for HER2-positive breast cancer is a safe and well-tolerated option in adjuvant setting.